1978
DOI: 10.1111/j.1524-4725.1978.tb00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratoacanthoma Recurrent After Surgical Excision

Abstract: A 62-year-old man developed a recurrent keratoacanthoma within two and a half weeks after grossly and microscopically complete removal of the primary tumor. X-irradiation of the recurrent lesion caused partial regression, and then intralesional injections of a suspension of triamicinolone caused final resolution of it. Although dermatologists generally practice partial destruction and surgeons almost always do total excision, neither method invariably cures this benign tumor, and repeated treatment may be nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Intralesional corticosteroids were also considered as a therapeutic option for KA, although the majority of results have shown that they were not as effective as other currently available alternatives (Belisario, 1965;Binitha, Najeeba, & Pabin, 2011;Burket & Caplan, 1964;Cipollaro, 1983;Consigli et al, 2000;Epstein Jr. & Epstein, 1978;Epstein, 2010;Ereaux & Schopflocher, 1965;Friedman, Morales, & Burnham, 1965;Jolly Jr. & Carpenter Jr., 1966;Kingman & Callen, 1984;McNairy, 1964;Reager, 1968;Reid & Cheesbrough, 1978;Sanders, Busam, Halpern, & Nehal, 2002). Unlike their classic mechanism of action, which utilizes their immunosuppressive effects, when treating KA, corticosteroids were suggested to exert their effects via different pathways.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Intralesional corticosteroids were also considered as a therapeutic option for KA, although the majority of results have shown that they were not as effective as other currently available alternatives (Belisario, 1965;Binitha, Najeeba, & Pabin, 2011;Burket & Caplan, 1964;Cipollaro, 1983;Consigli et al, 2000;Epstein Jr. & Epstein, 1978;Epstein, 2010;Ereaux & Schopflocher, 1965;Friedman, Morales, & Burnham, 1965;Jolly Jr. & Carpenter Jr., 1966;Kingman & Callen, 1984;McNairy, 1964;Reager, 1968;Reid & Cheesbrough, 1978;Sanders, Busam, Halpern, & Nehal, 2002). Unlike their classic mechanism of action, which utilizes their immunosuppressive effects, when treating KA, corticosteroids were suggested to exert their effects via different pathways.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Several other etiologic factors have been implicated in the formation of KA. These factors may be classified as follows: chemical carcinogens (tar, 25,26 pitch 26 ), mineral oil, 27 cigarettes, 15 trauma (body peel, carbon dioxide laser resurfacing, megavoltage radiation therapy, cryosurgery), 28,29 and immunosuppression 1,30 . Interestingly, Goldberg et al 31 .…”
Section: Pathogenesismentioning
confidence: 99%
“…In this case, corticosteroids also seemed to minimize scarring. Intralesional triamcinolone has been used to treat recurrence of keratoacanthoma after excision 22 and, theoretically, intralesional triamcinolone can be used to reduce the size of a keratoacanthoma, making it more amenable to excision. We presume the improvement noted in our patient was due to intralesional triamcinolone, but we cannot exclude the role of spontaneous regression.…”
Section: Discussionmentioning
confidence: 99%
“…An older literature describes the use of intralesional corticosteroids for solitary, multiple, or recurrent keratoacanthomas. 1,[14][15][16][17][18][19][20][21][22][23][24][25][26] Corticosteroids offer the advantages of immediately reducing inflammation and discomfort, while causing regression of up to 70% of keratoacanthomas with minimal scarring and systemic toxicity. 1 Murine papillomas induced by hydrocarbon application are thought to be similar to human keratoacanthomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation